Biodegradation of oil palm fibers using locally isolated fungi (Pycnoporus sanguineus) through plant biomechanics approach - Omar, Farah Nadia (2017)
Utilization of lignocellulosic OPEFB fiber has tremendously seen in Malaysia due to the cellulose and hemicellulose content. Conversion of these biopolymers into valuable products remains a challenging task with the presence of the recalcitrant lignin and scattering silica bodies on the fiber surface. Therefore, this study investigates the mechanical behaviour of the complex lignocellulosic OPEFB fiber containing silica bodies and provide an in-depth understanding of the delignification of OPEFB by fungi for further bioconversion into wide range of biomaterial applications. The microstructure of silica bodies on OPEFB fiber surface was modelled using finite element method, based on the results obtained from scanning electron microscope (SEM) images, tensile tests and X-ray microtomography (micro-CT) images. Silica body geometry, possible anisotropy/ orthotropy, debonding between the interface of the silica body and fiber, fiber thickness and presence of vascular bundle in the OPEFB were investigated through 2D and 3D models and analysed by commercial finite element software, Abaqus. In 2D model, silica bodies contribute on integrity or strength of the fiber, however, in the 3D model, the effect of silica bodies on the elasticity of the fiber was insignificant when the thickness of the fiber is larger than 0.2 mm. In the developed representative volume element (RVE) and micro-CT models, the simulation results show that the difference of the fiber model with and without silica bodies are larger under shear than compression and tension. However, in comparison to geometrical effect (silica bodies), lignin, cellulose, and hemicellulose components of the fiber are responsible for the complex mechanical and interface behavior of oil palm fibers.Hence, screening and isolation of lignin degrading fungi for deconstruction of lignin polymer in OPEFB was carried out. About 47 isolated fungi collected from environmental samples with six fungi were able to decolorize selective agar media, indicating possible presence of lignin-degrading enzymes; laccase and peroxidases. The highest producer of ligninolytic enzymes was identified as Pycnoporus sanguineus which able to utilize raw OPEFB fiber through solid state fermentation (SSF) with an increment of 1.37 folds of ligninolytic enzymes production as compared to submerged fermentation (SmF). Optimization study of different substrate pre-treatments (sodium hydroxide, Soxhlet extraction), incubation temperatures (20-40°C), ABTS concentrations (0-4%) and substrate amounts (3-15 g) on ligninolytic enzymes production was carried out. Results showed that the optimum conditions for P. sanguineus to produce highest laccase (15.49 U/g) with Klason lignin removal at 7.11% were using extractive-free OPEFB fiber, incubation temperature at 30°C, supplemented with 4 mM of ABTS and with 10 g of substrate loading size. Effectiveness of P. sanguineus for OPEFB degradation was further evaluated with the different ratio of fiber, fungi and palm oil mill effluent (POME) sludge as inoculum. The relationship between structural OPEFB fiber degradation and delignification process by P. sanguineus was studied through tensile testing data, enzymatic and lignin component data, and micro-CT images. The highest total lignin loss (35.81%) and total phenolic content produced (78.03%) was determined at a condition ratio of fiber to fungi (60:40), yielding of laccase and MnP of 0.18 and 0.02, respectively while production rate of laccase and MnP were 0.98 U/g/d and 0.11 U/g/d, respectively. Micro-CT results revealed that the delignification process damaged the fiber based on the volume reduction data where 14.11% of volume reduction was observed with treated fiber while 11.21% volume reduction was achieved with untreated fiber. It is suggested that P. sanguineus could be a potential lignin degrader of OPEFB fiber before being manipulated for other valuable products production.